2015
DOI: 10.1093/annonc/mdu490
|View full text |Cite
|
Sign up to set email alerts
|

Differences among young adults, adults and elderly chronic myeloid leukemia patients

Abstract: NCT00510926, NCT00514488, NCT00769327, NCT00481052.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 22 publications
7
64
0
1
Order By: Relevance
“…Recent data suggest that CML patients aged 5-29 years have less frequent cytogenetic and molecular responses to TKI therapy compared with older individuals and an increased risk of transformation to blast phase. 13,14 These data are consistent with our findings of an unfavorable impact of age on the probability of TFR. Others report a similar association.…”
Section: -12supporting
confidence: 92%
“…Recent data suggest that CML patients aged 5-29 years have less frequent cytogenetic and molecular responses to TKI therapy compared with older individuals and an increased risk of transformation to blast phase. 13,14 These data are consistent with our findings of an unfavorable impact of age on the probability of TFR. Others report a similar association.…”
Section: -12supporting
confidence: 92%
“…Recent studies reported a poorer prognostic profile in young adults (less than 30 years of age) as compared with other age groups. 37 38 This observation corresponds to our modelling of age in the ELTS score:…”
Section: Discussionsupporting
confidence: 78%
“…Its interpretation is not unequivocal and raises the question of the importance of age related phenomena such as the number, ability and speed of quiescent stem cells to enter cell cycle at different ages [25].…”
Section: Discussionmentioning
confidence: 99%